THE EFFECT OF THE PROJECT BASED LEARNING MODEL ON IMPROVING THE COMPETENCE OF PRACTICAL LEARNING OF VOCATIONAL STUDENTS: A REVIEW - Dewangga, Andrian Wisnu; Ahmad, Noesanto Dewantoro (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
This research aims to evaluate the effect of implementing the Project Based Learning (PjBL) Model on increasing the practical learning competence of Vocational High School students. Data collection was carried out through a literature review. This research is a literature review research that adopts a narrative review type, which aims to comprehensively investigate and analyze various scientific articles related to the research topic. Identify relevant literature, researchers conducted a search using the keyword "project-based learning model" on Google Scholar. Of the 13 journals found, 6 journals were not relevant and were excluded from the analysis. The results of this research indicate that project-based learning has the potential to be an effective method in improving students' practical skills in vocational schools, helping to build students' self-confidence in studying practical material, and providing a positive impact on students' participation in learning. The implication of this research is the importance of implementing PjBL as an effective learning strategy in improving vocational school students' competence in the context of practical learning